Ion Balance Measuring and Recording System for Air Ionizers: doi: 10.14456/mijet.2021.6 - Srisongkham, Suriyan; Photong, Chonlatee (Engineering Access, 2020)
Most electronic manufacturing processes require the control of Electro Static Discharge (ESD) for preventing products from damages. Air ionizers are one of the most popular devices used for controlling ESD due to their considerable cost and ease in using. However, all recent air ionizers could not measure ESD by real-time, as well as, could not automatically send measured values to the database wirelessly. Most industrial factories therefore utilize human to measure the ESD regularly as specified. This would not only lead to the lake of continuously control of ESD, but also disturb the manufacturing process and risk for high error measurement. This research presents an automatic, balanced ionizing measurement system for an air ionizer with wireless data sensing. The system consists of an analog ESD sensor, a microcontroller and a charge discharging sensor, that converts analog ESD signals into balanced ionizing values with sensor values with the decision coefficient (R2) equal to 0.944 The experimental results showed that the measured balanced ionizing values obtained from the proposed system provided low error in value between 3.067 volts - 6.957 volts in compared to the ion balance at 0 volts. The measured values could be converted into voltage in the range between -35 and +35 volts.